Orientasi Pendidikan Musik dalam Teori Multiple Intelligences - Sagaf Adzkia (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2024)
Purpose: This article aims to offer a comprehensive approach to understanding and developing students' potential in music education learning at school, oriented around Howard Gardner's Multiple Intelligences theory. By considering the diversity of individual intelligences, this approach creates an inclusive music learning environment. Verbal-linguistic, logical-mathematical, visual-spatial, kinesthetic, musical, interpersonal, and intrapersonal intelligences are each accommodated through various activities such as songwriting, lyric analysis, exploration of mathematical structures in music, creation of musical visualizations, musical gestures, and group work. Methods: This article uses a qualitative approach with conceptual understanding that presents ideas and justifications for music education concepts in order to provide original contributions in the form of key and logical arguments that are communicated effectively. Results and Discussion: The outcome of this article is a rationale that emphasizes the development of social skills, self-reflection, and active participation in various aspects of music education. Conclusion: Music education in the lens of Multiple Intelligences engages students holistically, creating learning experiences that blend artistic and cognitive elements, aligning music teaching and individual intelligences that foster students' comprehensive development in the context of music education in schools.